An Oncogenic Super-Enhancer Formed Through Somatic Mutation of a Noncoding Intergenic Element - Mansour, Marc R. (Science, 2014)
In certain human cancers, the expression of critical oncogenes is driven from large regulatory elements, called super-enhancers, which recruit much of the cell’s transcriptional apparatus and are defined by extensive acetylation of histone H3 lysine 27 (H3K27ac). In a subset of T-cell acute lymphoblastic leukemia (T-ALL) cases, we found that heterozygous somatic mutations are acquired that introduce binding motifs for the MYB transcription factor in a precise noncoding site, which creates a super-enhancer upstream of the TAL1 oncogene. MYB binds to this new site and recruits it’s H3K27 acetylase binding partner CBP, as well as core components of a major leukemogenic transcriptional complex that contains RUNX1, GATA-3, and TAL1 itself. Additionally, most endogenous super-enhancers found in T-ALL cells are occupied by MYB and CBP, suggesting a general role for MYB in super-enhancer initiation. Thus, this study identifies a genetic mechanism responsible for the generation of oncogenic super-enhancers in malignant cells.